Diagnostic Sensitivity of Plasma Endothelin-1 for Cerebral Vasospasm After Subarachnoid Hemorrhage, a Multicentre Double-Blind Study. (June 2022) - Bellapart, Judith; Nasrallah, Fatima; Winearls, James; Lassig-Smith, Melissa; Stuart, Janine; Boots, Rob; Winter, Craig; Flaws, Dylan; Bulmer, Andrew; Jones, Lee; Laupland, Kevin BjØrn
The purpose of this study is to establish the diagnostic sensitivity of Endothelin-1 for risk stratification and screening of clinical vasospasm after subarachnoid hemorrhage. This is a multicentre, observational study, correlating daily blood Endothelin-1 with clinical variables. Binary logistic regression used to examine if Endothelin-1 levels could be used to predict clinical vasospasm. Bivariate modelling used to explore associations between patient characteristics and vasospasm. A Receiver Operating Curve used to explore cut-off values for Endothelin-1. Sensitivity and specificity was used to validate the cut-point found in the pilot study. A total of 96 patients were enrolled over two years. Median Endothelin-1 was higher for patients who experienced clinical vasospasm except for day-5, where median endothelin for patients without vasospasm was higher (3.6 IQR = 5.3), compared to patients with vasospasm (3.3 IQR = 8.5) although differences were not significant. The Receiver Operating Curve analysis confirmed that day-5 Endothelin-1 was not a good indicator of vasospasm, with an area under the curve of 0.506 (95% CI: 0.350-0.663, p = 0.938). The levels of Endothelin-1 in blood do not discriminate patients who may develop symptomatic vasospasm. The high variability in Endothelin-1 levels, aligns with the pathophysiological variability of most biomarkers, decreasing their ability to predict a clinical event.